2005
DOI: 10.21273/jashs.130.6.848
|View full text |Cite
|
Sign up to set email alerts
|

Seed Storage Reserves and Glucosinolates in Brassica rapa L. Grown on the International Space Station

Abstract: Although plants are envisioned to play a central role in life support systems for future long-duration space travel, plant growth in space has been problematic due to horticultural problems of nutrient delivery and gas resupply posed by the weightless environment. Iterative improvement in hardware designed for growth of plants on orbital platforms now provides confidence that plants can perform well in microgravity, enabling investigation of their nutritional characteristics. Plants of B. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 27 publications
4
32
0
Order By: Relevance
“…Observations linking hypergravity exposure to an increase in lignin content resulted from exposure to much higher g -forces than those used in this study (e.g., 300g in Tamaoki et al, 2006 and135g in Hoson et al, 1996 ), and were made after incubation at 1g following a short hyperg exposure. Regardless, the decrease in 3-butenyl glucosinolate in response to increasing hypergravity supports previous work, in which glucosinolates in B. rapa plants grown in the microgravity conditions of the ISS increased compared to ground control plants ( Musgrave et al, 2005 ). 8 ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Observations linking hypergravity exposure to an increase in lignin content resulted from exposure to much higher g -forces than those used in this study (e.g., 300g in Tamaoki et al, 2006 and135g in Hoson et al, 1996 ), and were made after incubation at 1g following a short hyperg exposure. Regardless, the decrease in 3-butenyl glucosinolate in response to increasing hypergravity supports previous work, in which glucosinolates in B. rapa plants grown in the microgravity conditions of the ISS increased compared to ground control plants ( Musgrave et al, 2005 ). 8 ).…”
Section: Discussionsupporting
confidence: 88%
“…In previous studies, we also found that glucosinolates, secondary metabolites that contribute to distinctive fl avors and aromas of cruciferous plants, increased signifi cantly in stems of B. rapa grown in the microgravity conditions of the International Space Station (ISS) compared with the control plants ( Musgrave et al, 2005 ). In the current study, we examined this same class of compounds in hypergravity-grown plants, and in so doing, we tested the hypothesis that hypergravity increases the accumulation of cell wall polymers that are involved in plant structural support, which, in turn, leads to a decrease in nonstructural secondary metabolites in general.…”
Section: Methodsmentioning
confidence: 79%
“…Storage nutrients in Brassicaceae are proteins and lipids (Musgrave et al . ). A later experiment with the same objective on board the ISS confirmed previous data: spaceflight immature embryos had 24% less protein and 117% more starch than those of ground controls (Musgrave et al .…”
Section: Vegetative and Seed Reproductionmentioning
confidence: 97%
“…A later experiment with the same objective on board the ISS confirmed previous data: spaceflight immature embryos had 24% less protein and 117% more starch than those of ground controls (Musgrave et al . ). One reason for such changes in storage accumulation in microgravity could be differences in the closed gaseous microenvironment around the developing seeds.…”
Section: Vegetative and Seed Reproductionmentioning
confidence: 97%
See 1 more Smart Citation